IMPACT OF ARTERIAL HYPERTENSION ON COVID-19 - Cunha, Inês (2023)
Introduction: SARS-CoV-2 binds to host cells through the angiotensin-converting enzyme 2. Several studies have suggested that hypertensive individuals, due to the overexpression of this enzyme in alveolar epithelial cells, may have a higher risk of contracting COVID-19 and having a more serious illness. In fact, arterial hypertension has been described as one of the most frequent comorbidities in patients with COVID-19 and has been suggested to be associated with a worse prognosis, namely higher mortality. However, many initial studies did not consider some confounding factors such as age, gender and the presence of other comorbidities, making their integration extremely important to better clarify the real impact of arterial hypertension on the development and course of COVID-19. Objectives: Investigate the prevalence of arterial hypertension in patients hospitalized due to COVID-19 and the classes of antihypertensive agents used by them. Analyze in COVID-19 patients the differences between the group of hypertensive and non-hypertensive patients regarding demographic characteristics, prevalence of frequent comorbidities, namely diabetes mellitus and heart failure, main symptoms of COVID-19, blood test and arterial blood gas results, radiographic evidence of pneumonia, bacterial superinfection, admission to intensive care unit, length of stay and mortality rate. Analyze the relationship between systolic and diastolic blood pressure at emergency department admission with demographic characteristics, comorbidities, main symptoms of COVID-19, radiographic evidence of pneumonia, initiation of antibiotic therapy for suspected bacterial superinfection, admission to an intensive care unit and mortality rate. Material and Methods: Retrospective study of patients hospitalized due COVID-19, at Centro Hospitalar Tondela-Viseu, from March 15 to May 18, 2020, using data from the clinical files of SClinico and ALERT® and statistics analysis through SPSS®. Results: Of the 89 patients hospitalized for COVID-19 during the study period, 38.20% were women. The mean age was 73.26 ± 16.26 years; 38.20% of patients were institutionalized. Of the total sample, 55.06% had arterial hypertension. When comparing hypertensive vs non-hypertensive patients, it was found that hypertensive patients were significantly older (mean age 80 vs 65 years, respectively, p=0.0002). The percentage of women was significantly higher in the hypertensive group when compared to the non-hypertensive group (51.02 vs 22.50%, p=0.006). The prevalence of diabetes mellitus was significantly higher in the hypertensive group (42.86 vs 12.50%, p=0.002), as well as heart failure (42.86 vs 15.00%, p=0.004). Of the main symptoms of COVID-19, dyspnea was more frequent in the hypertensive group (57.14 vs 52.50%, p=0.661), but not cough (42.90 vs 57.50%, p=0.169), nor fever (44.90 vs 55.00%, p=0.343). There were no significant differences between groups regarding blood test and arterial blood gas results at emergency department admission, namely: leukocytes (10.5 vs 9.23 x 109/L, p=0.361), neutrophils (7.39 vs 7.09 x 109/L, p=0.801), lymphocytes (1.20 vs. 1.18 x 109/L, p=0.801), platelets (213.64 vs 207.15 x 109/L, p=0.723), C-reactive protein (7.99 vs 7.74 mg/dL, p=0.862), procalcitonin (1.82 vs 4.08 ng/ml, p=0.516), arterial pH (7.45 vs 7.44, p=0.715), lactates (1.77 vs 1.33 mmol/L, p=0.294) and the PaO2/FiO2 ratio (254.60 vs 278.26, p=0.211). The percentage of patients with radiographic evidence of pneumonia was identical in both groups (55.10 vs 65.00%, p=0.344), as well the start of antibiotic therapy for suspected bacterial superinfection (67.35 vs 62.50%, p=0.633). There were no significant differences in the need for admission to an intensive care unit (8.16 vs 15.00%, p=0.335). The average length of stay in the hospital was slightly higher in the hypertensive group (19.08 vs 14.95 days, p=0.173), but there were no significant differences in mortality (12.24 vs 17.50%, p=0.485). Conclusions: As described in the literature, arterial hypertension was highly prevalent in our sample and these patients were, on average, older and had more comorbidities. Even so, no significant differences were found in the clinical presentation, blood tests and radiographic changes, nor in the disease severity and prognosis.